Intraluminal gastrointestinal stromal tumor leading to intussusception in an adult (Indian Journal of Case Reports, 2024)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the abdomen. Most of these tumors occur in the stomach. They arise from the interstitial cells of Cajal. GIST usually occurs in adults of more than 50 years of age, with a median age of 62–63 years. Fewer than 10% of cases occur at <40 years of age. It commonly presents as exophytic growth. GIST may lead to symptoms due to the effect of the mass. Mucosal ulceration may cause blood loss leading to anemia. Asymptomatic GIST may be discovered as an incidental finding during imaging or endoscopy. Intraluminal GIST presenting clinically as intussusception is extremely rare. This case report presents a case of intestinal GIST in a 35-year-old man. The tumor presented as an intraluminal nodule leading to intussusception. A complete resection of the tumor was done. Histopathological examination with immunohistochemistry helped to arrive at a definite diagnosis and determine the prognosis.